Analyzing System Reliability Across Configurational Diversity and Component Variability: Insights From Reliability Block Diagrams and Event Space Method - Jaipurkar, Nikhil Vikas; Sisodiya, Ram Naresh B. S. (Communications in Mathematics and Applications, 2024)
In this study, we systematically investigated the reliability of a complex system configured in multiple ways with diverse components, employing both Reliability Block Diagram and Event Space Method. Our approach involved evaluating component reliability in series and parallel arrangements, with a subsequent consolidation of these assessments. The primary aim was to set a benchmark forquantifying system reliability across various configurations and conditions. The study outcomes are illustrated using graphs and tables, facilitating a comparative analysis of system reliability across diverse setups.
Keywords: Reliability; Failure rate; Event space method; Reliability block diagram